7. Professor of Art Paradigms: Theoretical and Applied Approaches - Bularga Tatiana (Sciendo, 2017)
The present article describes purposes, learning content and requirements of an educational academic and postgraduate (internships for teachers) process, focused on teacher training in respect of the most subtle and valuable framework for education, the achievement of the individual potential of each pupil, qualified as a unique personality. Therefore, it is proposed a synthesis on the formative program geared towards the assimilation of the future and current teachers of artistic disciplines (music, choreography, painting) of the action and behavioral models appropriate to the domain, to the effectively organization of individualized educational process.